Evaluation of Hospitalized Patient Outcomes in COVID-19 Infection for Continued versus Discontinued Use of Preadmission Antiplatelet Regimen. (June 2023) - Antoniello, Angela; Brophy, Alison; Opsha, Yekaterina
Objective: In SARS-CoV-2 (COVID-19) infection, it is unclear if continuation of preadmission antiplatelet regimens upon hospitalization will improve hypercoagulability outcomes.Methods: This retrospective cohort study analyzed adult patients hospitalized with confirmed COVID-19 infection for a 6-week period from March 13, 2020, to April 27, 2020. Preadmission antiplatelet regimen continuation for less than 75% of admission was compared to continuation for at least 75% of admission. Pregnancy, either death or withdrawal of care within 24 hours of admission, and admission beyond the studied timeframe were excluded. The primary endpoint was difference in World Health Organization COVID-19 Ordinal Scale for Clinical Improvement values (World Health Organization [WHO] scores) between maximum score during admission to that upon discharge. Secondary endpoints were mechanical ventilation requirement, mortality, radiologically confirmed venous thromboembolism, major bleeding, and length of stay.Results: This study included 171 patients. Patients failing to continue antiplatelet regimens for at least 75% of admission (n = 76) had significantly worse WHO score differences than those who did (n = 95) (median −1 vs 2; P < .05). Mechanical ventilation requirement (57% vs 27%; P < .05) and mortality (58% vs 29%; P < .05) also favored antiplatelet continuation. All other endpoints were not significantly different.Conclusion: Significantly improved WHO scores, mechanical ventilation requirement, and mortality occurred in patients continuing preadmission antiplatelet regimens in COVID-19 infection. Future prospective studies of COVID-19 patients with consistently collected baseline hypercoagulability markers (platelets, D-dimer, fibrinogen, and coagulation studies) and similar severe disease risk factors are required to confirm potential benefits of antiplatelet therapy during hospitalization.